Nursing staff and supervisors perceptions on stress and resilience: a qualitative study - Helaß, Madeleine; Greinacher, Anja; Genrich, Melanie; Müller, Andreas; Angerer, Peter; Gündel, Harald; Junne, Florian; Nikendei, Christoph; Maatouk, Imad (BMC nursing, 2025)
Background: Supervisor–subordinate relationship is high relevant in dealing with work-related stress and providing a compassionate, high-quality, and safe nursing care while meeting the needs of the hospital. Our aim was to assess the predisposing risk and resilience factors of the stress of nursing staff as well as to explore the common and distinctive perceptions of these factors between nurses without a managerial position (nursing staff ) and employees in a supervising position (nurse managers, ward nurses). Design: Generic qualitative study using half-standardized interviews. Methods: Fifty nurses and supervisors from different departments from a German hospital of maximum medical care participated in this study between August and November 2018. Nineteen face-to-face interviews and five focus groups were conducted. Transcripts were subjected to structured qualitative content analysis. Results Systematised in Lazarus’s transactional model, nurses, and supervisors mentioned similar risk and resilience factors of stress. Disagreement in suggested responsibility for nurses’ stress or health and an evaluation of implemented measures meeting the nurses’ needs are discussed. Conclusion: Nursing staff and supervisors should enforce exchange to reduce disagreements in perceptions and to improve mutual understanding. Furthermore, measures to meet nurses’ needs to minimize stress and to improve collaboration and job satisfaction should be developed in close coordination with the target group. The focus should be placed on restructuring training and education programs with supplementation of self-responsibility promotion.
Gesehen am 25.09.2025